PUSAT KEGIATAN SELAM KALIMANTAN SELATAN - Irfansyah, Dearby Lintang Putri; Nurfansyah, Nurfansyah; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
South Kalimantan has great underwater potential, water accidents often occur in South Kalimantan and the needs for marine tourism in South Kalimantan do not coincide with the pre-existing diving facilities. Diving activities also have quite good interest but have experienced a decline and the Dive Center that has been established still has incomplete infrastructure facilities, so a complete space is needed to attract public interest in diving activities. So that the use of the concept of education and recreation for the Dive Center can become a place to practice and learn as well as introduce and develop diving activities. The aim of this design is to develop an existing Dive Center so that it is able to accommodate training and learning activities as well as being an educational and recreational facility with a functional architectural approach. It is hoped that the existence of this Dive Center can meet the needs, develop and introduce diving activities to the community.